Phenomena of Moral Education Among High School Students in Garut District - Sarbini (GoAcademica Research & Publishing, 2022)
This study aims to examine the phenomenon of moral education among students in the Generation Z era. The study was conducted in Garut Regency by applying a qualitative approach and descriptive method. Data collection was carried out on 30 (thirty) selected informants, 24 (twenty-four) students, 3 (three) teachers, and 3 (three) parents of students. Research has found that moral education among Generation Z students has major challenges. In addition to students being faced with technological developments that facilitate access to information and learning, technology also has many negative impacts. Students who are able to apply this moral education will be able to control technology as a learning medium. On the other hand, students who do not have sufficient moral education will be controlled by the environment and technology. This study concludes that the challenges of moral education are related to students' ability to apply them in the realities of life.